STUDI KOMPETENSI MULTIREPRESENTASI MAHASISWA PADA TOPIK INTERFERENSI DAN DIFRAKSI - Kenny Setiawan Lahope; Djeli Alvi Tulandi; Satyano Wim Mongan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
The study is conducted with the ability to representation in understanding the concept of interference and diffraction. The purpose of this research is to map the ability of student representation. The types of representations used in this research are verbal representation, visual representation, and mathematical representation. Research is conducted using analytic descriptive methods. The study was conducted in the Manado state university physics department during the V semester of the 21-student physics education course. The data-gathering techniques use essays which consist of verbal, visual, and math. By research, it was found that the ability to the student was divided into three categories that were the singular representation category, the dual representation category, and the complex representation category. Data analysis shows a 9.5% for single representational ability category, 47.6 % category double representational ability, and 42.9% category complex representational ability. Therefore, a student's dual capacity of representation is more dominant than a single representation and complex representation